2019
DOI: 10.1038/s41598-019-45786-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of the novel endogenous promoter HASP1 and its signal peptide from Phaeodactylum tricornutum

Abstract: Although diatoms have been extensively studied as bioreactors, only a limited number of efficient gene promoters are available. Therefore, the development of new endogenous promoters is important for the heterologous production of a variety of recombinant proteins. Herein, we identified the most abundant secreted protein in Phaeodactylum tricornutum , designated ‘highly abundant secreted protein 1’ (HASP1), and characterised the activities of its promoter and signal peptide using green f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…We detected an eGFP signal only under phosphate-limited conditions, indicating that the regulatory regions of PtPhos2 might be useful also for regulated gene expression in synthetic approaches. This was also recently proposed by another group; however, P i regulation was not observed, most likely because of the small size of the analyzed upstream region (499 bp) (Erdene-Ochir et al, 2019).…”
Section: Extracellular Phosphate Mobilizationsupporting
confidence: 80%
See 2 more Smart Citations
“…We detected an eGFP signal only under phosphate-limited conditions, indicating that the regulatory regions of PtPhos2 might be useful also for regulated gene expression in synthetic approaches. This was also recently proposed by another group; however, P i regulation was not observed, most likely because of the small size of the analyzed upstream region (499 bp) (Erdene-Ochir et al, 2019).…”
Section: Extracellular Phosphate Mobilizationsupporting
confidence: 80%
“…We identified four enzymes acting most likely extracellularly (Figures 1-4): PtPhos1, 2, 3, and 8. Two of these, PtPhos1, a PhoA-like phosphatase, and PtPhos2, having a predicted phytase-like domain, are secreted enzymes (Figure 1), first identified by analyzing the medium for secreted proteins (Lin et al, 2013;Buhmann et al, 2016;Erdene-Ochir et al, 2019). Interestingly, both enzymes differed significantly in their molecular mass determined by Coomassie-stained SDS-PAGE gels and the use of prediction tools, respectively.…”
Section: Extracellular Phosphate Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely the case that at least some of these compounds are not imported into the diatom cell, but instead hydrolyzed by extracellular alkaline phosphatases to generate P i in direct surrounding. Localization studies with putative P-responsive alkaline phosphatases support this concept and for Phatrdraft_49678 and 47612 secretions of the enzymes were described (Buhmann et al 2016;Erdene-Ochir et al 2019;Lin et al 2013). In addition, Flynn and coworkers measured alkaline phosphatase activity in diverse cell fractions and found that it might be associated with the cell surface, extracellular medium, and plasma membrane, respectively (Flynn et al 1986).…”
Section: Introductionmentioning
confidence: 89%
“…The Chlamydomonas RPL23 flanking sequence, which was selected as having uniformly high expression levels based on the analysis of a large set of diurnal transcriptome data, was shown to stably express the LhcSh fusion gene (luciferase and zeocin resistance gene) at significantly higher levels than that of AR or the psaD promoter 19 . Promoter HASP1 (highly abundant secreted protein 1) was selected as the most abundant secreted protein based on proteome profiling of the culture medium of Phaeodactrium tricornutum using LC-MS/MS analysis, and as a result, its activity on GFP expression was observed during all growth phases 20 . However, because commonly used promoters and transformation conditions have rarely adapted to microalgae, these approaches need to be investigated in interesting strains as species-specific methods.…”
mentioning
confidence: 99%